MicroRNA-1 Expression and Function in Hyalomma Anatolicum anatolicum (Acari: Ixodidae) Ticks - Luo, Jin; Ren, Qiaoyun; Liu, Wenge; Qiu, Xiaofei; Zhang, Gaofeng; Tan, Yangchun; Cao, Runlai; Yin, Hong; Luo, Jianxun; Li, Xiangrui; Liu, Guangyuan (Frontiers in Physiology, 2021)
MicroRNAs act as mRNA posttranscriptional regulators, playing important roles in cell differentiation, transcriptional regulation, growth and development. In this study, microRNA expression profiles of Hyalomma anatolicum anatolicum ticks at different developmental stages were detected by high-throughput sequencing and functionally assessed. In total, 2,585,169, 1,252,678, 1,558,217 and 1,155,283 unique reads were obtained from eggs, larvae, nymphs and adults, respectively, with 42, 46, 45 and 41 conserved microRNAs in these stages, respectively. Using eggs as a control, 48, 43 and 39 microRNAs were upregulated and 3, 10 and 9 downregulated in larvae, nymphs and adults, respectively. microRNA-1 (miR-1) was expressed in high abundance throughout Ha. anatolicum development, with an average of nearly one million transcripts, and it is highly conserved among tick species. Quantitative real-time PCR (qPCR) showed that miR-1 expression gradually increased with tick development, reaching the highest level at engorgement. Differential tissue expression was detected, with significantly higher levels in the salivary glands and epidermis than in the midgut. Inhibition assays showed no significant change in body weight or spawning time or amount between experimental and control groups, but there was a significant difference (p<0.01) in engorgement time. With miR-1 inhibition, ticks displayed obvious deformities during later development. To more fully explain the microRNA mechanism of action, the miR-1 family was analyzed regarding target gene; members acting on Hsp60 include miR-5, miR-994, miR-969, and miR-1011, which jointly play a role. Therefore, microRNAs are critical for normal tick development, and the primary structure of the mature sequence of miR-1 is highly conserved. Nonetheless, different developmental stages and tissues show different expression patterns, with a certain role in prolonging feeding. miR-1, together with other family members, regulates mRNA function and may be used as a molecular marker for species origin and evolution analysis and internal reference gene selection.